The three dependency interpretation - Bresser-Pereira, Luiz Carlos (Universidade Estadual Paulista / UNESP, 2011)
In the 1950s two groups of public intellectuals, organized around ECLAC, in Santiago, Chile, and ISEB, in Rio de Janeiro, pioneered the thinking on Latin American societies and on its industrialization from a nationalist standpoint. ECLAC mainly criticized the law of comparative advantage; ISEB focused on the class coalition behind the proposed national-developmentalist strategy. The idea of a national bourgeoisie was key to this interpretation. Yet, the Cuban revolution and the following military coups in the South Cone made room for criticism of these ideas by the Marxist dependency interpretation which soon was divided in three: the overexploitation, the national-dependency contradiction, and the associated dependency interpretation. The later ignored the ambiguous and contradictory character of the Latin-American bourgeoisie asserted by the national-dependent interpretation,turned dominant in the region, contributed to the loss of the idea ofnation by the Brazilian intellectuals, and represented an obstacleto the definition of a national-development strategy.